2019
DOI: 10.1088/1742-6596/1387/1/012146
|View full text |Cite
|
Sign up to set email alerts
|

The Running-based Anaerobic Sprint Test of different Type of Sports

Abstract: The aim of study was to compare the anaerobic capacity of different type sport. The running-based anaerobic capacity test (RAST) were exam to 42 athletes of football (10), sprint (6), takraw (8), volleyball (10) and pencak silat (8). The anova analysis resulted the difference of minimum power (MinP) (p=0.001), maximum power (MaxP) (p=0.000), average power (AvP)(0.000) and fatigue index (FI) (0.008). The post hoc analysis showed no difference anaerobic capacity between athletes of football vs sprinter, football… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Also, there are several studies in the literature expressing reservations about the reliability of SpO 2 in situations leading to deep hypoxemia (Pottecher et al, 2003), indicating that the SpO 2 results during the BHs should be interpreted with caution. Third, fatigue index values were rather low compared to other studies: 7.1 in students of physical education and sport exercise (Paradisis et al, 2005), 5.4 after a power endurance training in basketball players (Balčiunas et al, 2006), 8.1-10.5 in elite basketball players (Pojskić et al, 2015), 4.2 in football players, 4.2 in sprinters, 4.2 in takrawer, 2 in volleyballers, and 4.6 in Pencak Silater athletes (Nasuka et al, 2019). The results could have been different if the participants had reached higher FI.…”
Section: Limitationsmentioning
confidence: 68%
“…Also, there are several studies in the literature expressing reservations about the reliability of SpO 2 in situations leading to deep hypoxemia (Pottecher et al, 2003), indicating that the SpO 2 results during the BHs should be interpreted with caution. Third, fatigue index values were rather low compared to other studies: 7.1 in students of physical education and sport exercise (Paradisis et al, 2005), 5.4 after a power endurance training in basketball players (Balčiunas et al, 2006), 8.1-10.5 in elite basketball players (Pojskić et al, 2015), 4.2 in football players, 4.2 in sprinters, 4.2 in takrawer, 2 in volleyballers, and 4.6 in Pencak Silater athletes (Nasuka et al, 2019). The results could have been different if the participants had reached higher FI.…”
Section: Limitationsmentioning
confidence: 68%
“…Running-based anaerobic sprint test is a test to measure the capacity of the anaerobic athlete (Santosa et al, 2019). Running-based anaerobic sprint tests can describe maximum and minimum power and the fatigue index of athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research by Santosa et al (2019) showed that Sprinter has the highest power and fatigue index values. Senior-level athletes showed that the opposite hitter still has the highest power value, middle blocker in the second place, outside hitter in the third place, setter in the fourth place, and libero has the lowest power value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penelitian sebelumnya menunjukkan bahwa rata-rata kapasitas anaerobik atlet pencak silat dalam kategori bagus atau penelitian sebelumnya menunjukkan bahwa rata-rata kapasitas anaerobik atlet pencak silat dalam kategori Bagus atau 4,646 (Nasuka et al, 2019). Tentunya hal ini perlu ditingkatkan lagi supaya atlet memiliki kapasitas anaerobik yang lebih baik baik.…”
Section: Pendahuluanunclassified